Globalization and national identity: a qualitative approach - Hira Amin (6203567) (2025)
Studies show an ambivalent relationship between globalization and national identity. Waves of national populism and counter-movements have emerged. Each country is grappling with its own internal debates and trajectories. In the context of Qatar, studies based mainly on quantitative surveys have documented a steadily growing pride in Qatari national identity. Nevertheless, fear of dilution or loss of traditions and culture regularly punctuates national debates and informs policy. This paper adds to this discussion by bringing in more granular, bottom-up experiences through in-depth photovoice interviews with thirty young Qataris. It highlights two different pathways that are strengthening national identity amongst the youth. First, the strong role of the family and community in ensuring successful socialization and transmission of key facets of Qatari identity, namely Arabic language, Islamic traditions, and Arab customs. Second, educational opportunities as well as digital spaces have enabled intercultural mixing that led to a process of self-reflection and discovery by acting as ambassadors and witnessing their relative privilege. This resulted in a stronger attachment to their Qatari identity. This study adds to the discussions on national identity formation and the role of family socialization practices, the internationalization of education, and cross-cultural communication. Other Information Published in: National Identities License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/14608944.2025.2588266